Was ist die Standardform von y = (x-5) (x + 6) ^ 2 - (x-5) ^ 2 (x + 6)?

Was ist die Standardform von y = (x-5) (x + 6) ^ 2 - (x-5) ^ 2 (x + 6)?
Anonim

Antworten:

#y = 11x ^ 2 + 11x-330 #

Erläuterung:

#y = (x-5) (x + 6) ^ 2 - (x-5) ^ 2 (x + 6) #

#Farbe (weiß) (y) = (x-5) (x + 6) ((x + 6) - (x-5)) #

#Farbe (weiß) (y) = (x-5) (x + 6) (Farbe (rot) (Abbruch (Farbe (schwarz) (x))) + 6-farbig (rot) (Abbruch (Farbe (schwarz)) (x))) + 5) #

#Farbe (weiß) (y) = 11 (x-5) (x + 6) #

#Farbe (weiß) (y) = 11 (x ^ 2 + x-30) #

#Farbe (weiß) (y) = 11x ^ 2 + 11x-330 #